2020
DOI: 10.3390/ijerph17217821
|View full text |Cite
|
Sign up to set email alerts
|

Challenges When Evaluating Cognitive Bias Modification Interventions for Substance Use Disorder

Abstract: In recent years, advances in experimental psychology have led to a better understanding in automatic, unconscious processes, referred to as attentional and approach biases amongst individuals with substance use disorders. Attentional biases refer to the relatively automatic tendencies for attention to be preferentially allocated towards substance-related cues. Whereas, approach bias refers to the relatively automatic behavioral tendencies of individuals to reach out to substance-related cues in their natural e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…Notably, CBM interventions and its application to subjects with SUD are not without challenges. For example, it has been observed that the existence and magnitude of cognitive biases show a high interindividual variability and CBM interventions are highly dependent on the selection of the appropriate task for bias assessment and modification (see [57]). DOI: 10.1159/000525268…”
Section: Discussionmentioning
confidence: 99%
“…Notably, CBM interventions and its application to subjects with SUD are not without challenges. For example, it has been observed that the existence and magnitude of cognitive biases show a high interindividual variability and CBM interventions are highly dependent on the selection of the appropriate task for bias assessment and modification (see [57]). DOI: 10.1159/000525268…”
Section: Discussionmentioning
confidence: 99%